2016
DOI: 10.1021/acs.jpcb.6b10668
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Nitrogen-Pyramidalized Bicyclic β-Proline Oligomers: Length-Dependent Convergence to Organized Structures

Abstract: In this study, the solution structures of the homooligomers of a conformationally constrained bicyclic proline-type β-amino acid were studied by means of molecular dynamics (MD) calculations in explicit methanol and water using the umbrella sampling method. The ratio of trans-amide and cis-amide was estimated by NMR and the rotational barrier of the amide of acetylated bicyclic amino acid monomer was estimated by two-dimensional (2D) exchange spectroscopy (EXSY) or line-shape analysis. A bias potential was int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…This is in good agreement with the value of approximately 19 kcal·mol −1 calculated from the analysis of the 1 H line shapes of tetramer 1 tert -butyl signals in NMR spectra recorded in the temperature range between 298 and 408 K (Supplementary Figure 5 ). This value is also in good aggreement with ΔG measured for Z↔E transition in acetyl-L-proline-NHMe (20.4 kcal·mol −1 ) (Doshi and Hamelberg, 2009 ), acetyl-L-proline-OMe (21.1 kcal·mol −1 ) (Renner et al, 2001 ) and in nitrogen-pyramidalized bicyclic β-proline oligomers (17.8 kcal·mol −1 ) (Otani et al, 2017 ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This is in good agreement with the value of approximately 19 kcal·mol −1 calculated from the analysis of the 1 H line shapes of tetramer 1 tert -butyl signals in NMR spectra recorded in the temperature range between 298 and 408 K (Supplementary Figure 5 ). This value is also in good aggreement with ΔG measured for Z↔E transition in acetyl-L-proline-NHMe (20.4 kcal·mol −1 ) (Doshi and Hamelberg, 2009 ), acetyl-L-proline-OMe (21.1 kcal·mol −1 ) (Renner et al, 2001 ) and in nitrogen-pyramidalized bicyclic β-proline oligomers (17.8 kcal·mol −1 ) (Otani et al, 2017 ).…”
Section: Resultssupporting
confidence: 83%
“…Several attempts to achieve certain conformational control by substitution or bridging of pyrrolidine rings in the β-polyproline scaffold were reported (Otani et al, 2006 ; Krow et al, 2010 ; Wang et al, 2014 ). Circular dichroism (CD) (Huck et al, 1999 ; Kim et al, 2000 ; Caumes et al, 2013 ), X-ray crystallography (Krow et al, 2010 ; Kudryavtsev et al, 2013 , 2015a ; Wang et al, 2014 ), NMR spectroscopy (Huck et al, 2003 ; Krow et al, 2010 ; Caumes et al, 2013 ; Wang et al, 2014 ; Kudryavtsev et al, 2015a , b ) and quantum mechanics calculation (Otani et al, 2006 , 2017 ; Wang et al, 2014 ) revealed the formation of ordered structures in solution and solid state for the reported β-proline oligopeptides and indicated the presence of an equilibrium between several dominant conformations in solution.…”
Section: Introductionmentioning
confidence: 99%
“…3b, Table 2, Supplementary Figs. 8–13) 39,40 . The free energies of rotation (∆ G t → c ‡ and ∆ G c → t ‡ ) were obtained from the enthalpy of activation (∆ H ‡ ) and the entropy of activation (∆ S ‡ ), which were derived from the slope and intercept of the Eyring plot of the rate against temperature (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Our further structural studies revealed that homooligomers of either cisor trans-amide can fold themselves into corresponding highly ordered helices. [4][5][6][7] Moreover, unlike α-amino acid peptides, which are significantly stabilized by intramolecular hydrogen bonding, these helical structures are self-organized and conformationally stable without the aid of hydrogen bonding and irrespective of solvent (protic/aprotic/halogenated) or temperature. Combination of these bicyclic β-proline analogues and α-amino acids, that is, heterooligomers are also synthetically accessible, and the N-amide bond of these bicyclic β-proline analogues are reluctant to alkaline hydrolysis, indicating some metabolic stability.…”
Section: Introductionmentioning
confidence: 99%